1992
DOI: 10.2527/1992.7051326x
|View full text |Cite
|
Sign up to set email alerts
|

Trenbolone acetate/estradiol combinations in feedlot steers: dose-response and implant carrier effects2

Abstract: Two experiments were conducted at three locations to determine the correct dosage and carrier for trenbolone acetate (TBA) and estradiol (E2) implants in feedlot steers. In the dose-response experiment, 1,296 steers were allotted to six implant treatments (48 pens per location): control, 140 mg of TBA (140/0), 30 mg of E2 (0/30), 20 mg of TBA + 4 mg of E2(20/4), 80 mg of TBA + 16 mg of E2(80/16), and 140 mg of TBA + 28 mg of E2 (140/28). In the carrier experiment, 575 steers were allotted to five implant treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(37 citation statements)
references
References 3 publications
(5 reference statements)
6
30
0
1
Order By: Relevance
“…Our findings for LMA on d 115 were similar to other reports that have shown increased LMA in steers implanted with a combined implant containing 140 mg of TBA and 28 mg of E 2 (Eversole et al, 1989;Bartle et al, 1992). In contrast, Perry et al (1991) found that TBA+E 2 (140/28) had no effect on LMA in steers from various breed groups.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our findings for LMA on d 115 were similar to other reports that have shown increased LMA in steers implanted with a combined implant containing 140 mg of TBA and 28 mg of E 2 (Eversole et al, 1989;Bartle et al, 1992). In contrast, Perry et al (1991) found that TBA+E 2 (140/28) had no effect on LMA in steers from various breed groups.…”
Section: Discussionsupporting
confidence: 90%
“…However, the TBA+E 2 -implanted steers always maintained greater gains than nonimplanted steers regardless of the stage of the feeding period. Administration of separate TBA and E 2 implants at various doses and combining TBA+E 2 at a higher dose (140/28) have resulted in increases of 18 to 25% in ADG and an average improvement in feed efficiency of 10 to 18% in implanted steers relative to nonimplanted steers (Schanbacher, 1984;Eversole et al, 1989;Anderson, 1991;Perry et al, 1991;Bartle et al, 1992). Although we cannot compare our results directly to previous reports with different combinations of TBA and E 2 , our survey of the literature suggests that expected differences in performance are similar regardless of whether steroids are delivered separately or from a combined implant.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major focus of this study was to determine the impact of delaying the initial feedlot implant on QG in calf-fed steers. When evaluating previous research, studies have shown that the use of implants has little or no effect on MS or QG (Bartle et al, 1992;Gerken et al, 1995), whereas other studies have shown a substantial reduction in MS and QG (Foutz et al, 1990;Senn and Wagner, 1994). In previous work using delayed implant programs in calves fed for 212 d, Samber et al (1996) demonstrated no difference in MS or QG from 2 delayed implant programs compared with control nonimplanted cattle; however, MS and QG were both decreased in calves implanted with 3 successive implants.…”
Section: Carcass Characteristicsmentioning
confidence: 99%
“…Trenbolone acetate is a synthetic analog of testosterone which is widely used in the US and Canada (8). Implanted trenbolone in steers enhances animal growth performance and increases muscle mass (9-12). To date, however, the underlying mechanisms for the biological effect of testosterone on muscle growth are not very clear.…”
Section: Introductionmentioning
confidence: 99%